The Ocean Incubator Network (OIN) Living Laboratory and Ocean Literacy Toolkit - Poto, Margherita Paola; Vita, Laura; Brown, Katrina; Hayden-Nygren, Juliana; Heinrich, Katharina; Hernández Ant, Alba; Kuhn, Annegret; Montaña Monoga, Ana Maria; Murray, Emily Margaret; Pandeva, Rada; Panieri, Giuliana; Parry, Sarah; et al. (Septentrio Reports, 2024)
The report documents the experience and knowledge gained during the Ocean Incubator Network workshop on Ocean Literacy, led by Margherita Paola Poto and Laura Vita. The event was held at the Arctic House in Copenhagen and funded by UArctic UiT, The Arctic University of Norway, over May 2-4, 2024. The workshop was organized as a dynamic living laboratory facilitating active participation and contribution from the Ocean Incubator Network members. Structured over three days, the workshop’s agenda followed two thematic pathways: connecting with each other and connecting with the ocean. This work resulted from the culmination of a series of preparatory meetings spanning from September 2023 (with a kick-off in Tromsø) to April 2024 (Monthly Coffee Meetings).